A persuasão em artigos de opinião: um enfoque da gramática sistêmico-funcional - Silva, Daniela Costa da (2015)
The act of arguing, guiding discourse in order to persuade the interlocutor, constitutes a fundamental linguistic act. This study aims to compare two opinion articles one by Roberto Pompeu de Toledo, from Veja Magazine, and one by Bárbara Gancia, from Folha de São Paulo News to examine their persuasion style. Persuasion, either via conviction or via seduction, is based on three rhetorical modes: narration, description and argumentation. Arguments can draw on narration and description to cope with verifiable statements to ensure the veracity of the information that the argument makes use of. Persuasion, on the other hand, is based on the evaluation of facts and people. For this reason, I turn to the notion of Appraisal (Martin, 2000) through which writers express underlying ideologies and invite readers to agree with their opinion. The critical analysis to be carried out will be supported by Systemic Functional-Grammar (Halliday, 2004), encompassing both Critical Linguists and Appraisal. The research seeks to answer the following questions: (a) How is the genre structure formed in the rhetorical modes in Gancia s and Toledo's texts? (b) What kind of persuasion style conviction or seduction prevails in each text? (c) What is the contribution of Appraisal to the construction of persuasion in these texts? The research shows that, although Bárbara Gancia and Pompeu de Toledo wrote about the same theme Pope Benedict XVI's resignation , their criticism towards the situation is presented in different ways: Gancia depreciates the Church through their representatives whereas Toledo criticizes the image of the Pope, and, by extension, the Church